A sensitive and selective enzyme-free amperometric glucose biosensor using a composite from multi-walled carbon nanotubes and cobalt phthalocyanine. Issue 34 (15th April 2015) - Devasenathipathy, Rajkumar; Karuppiah, Chelladurai; Chen, Shen-Ming; Palanisamy, Selvakumar; Lou, Bih-Show; Ali, M. Ajmal; Al-Hemaid, Fahad M. A.
<x xml:space="preserve">Abstract</x> In the present study, a simple and sensitive amperometric enzyme-free glucose sensor was developed at a multiwalled carbon nanotube and cobalt phthalocyanine (MWCNT–CoTsPc) modified electrode.